SANS Study of Highly Resilient Poly(ethylene glycol) Hydrogels - Saffer, Erika M. (2014)
Polymer networks are critically important for numerous applications including soft biomaterials, adhesives, coatings, elastomers, and gel-based materials for energy storage. One long-standing challenge these materials present lies in understanding the role of network defects, such as dangling ends and loops, developed during cross-linking. These defects can negatively impact the physical, mechanical, and transport properties of the gel. Here we report chemically cross-linked poly(ethylene glycol) (PEG) gels formed through a unique cross-linking scheme designed to minimize defects in the network. The highly resilient mechanical properties of these systems (discussed in a previous publication(1)), suggests that this cross-linking technique yields more homogeneous network structures. Four series of gels were formed based on chains of 35,000 g/mol, (35K), 12,000 g/mol (12K) g/mol, 8,000 g/mol (8K) and 4,000 g/mol (4K) PEG. Gels were synthesized at five initial polymer concentrations ranging from 0.077 g/mL to 0.50 g/mL. Small-angle neutron scattering (SANS) was utilized to investigate the network structures of gels in both D(2)O and d-DMF. SANS results show the resulting network structure is dependent on PEG length, transitioning from a more homogeneous network structure at high molecular weight PEG to a two phase structure at the lowest molecular weight PEG. Further investigation of the transport properties inherent to these systems, such as diffusion, will aid to further confirm the network structures.